Clutter supression in passive coherent radar systems - Řezníček, Michal; Bezoušek, Pavel; Shejbal, Tomáš (Croatian Society Electronics in Marine - ELMAR, 2016)
In this paper least mean squares methods application to ground clutter echoes suppression in bistatic radar systems are described. Tests of LMS and NLMS filters on real data are presented and their effectiveness for ground clutter echoes suppression is discussed. Finally it was found that the ground clutter echoes suppression effectiveness is highly deteriorated by ground clutter echoes presence in the reference signal.
Potlačení nežádoucích odrazů pro bistatický radiolokátor
Keywords: Adaptive Filter; Bistatic radar; Ground Clutter; Signal processing; LMS; NLMS; Adaptivní filtr, Bistatický radar, Pozemní clutter, Zpracování signálu, LMS, NLMS